2020
DOI: 10.1002/pra2.254
|View full text |Cite
|
Sign up to set email alerts
|

Librarian perspectives on the role of virtual reality in public libraries

Abstract: This paper explores librarians’ perception of virtual reality as well as opportunities and challenges associated with implementing VR in public libraries. We interviewed 36 librarians who developed and offered VR programs as part of the research project, before and after the programming. The findings show how VR may be used in the public library as a learning tool and technology that encourages social interactions. Librarians discuss how the unique qualities of VR such as immersion and interactivity of VR make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…However, for perceived competence, students also feel that virtual reality could improve the knowledge and skill as well as the effort more than traditional text-based materials. The result is aligned with [36] in the context of librarian in public library and also consistent with the research findings of [34], [35] to improve intrinsic motivation for training nurse and medical students.…”
Section: Discussionsupporting
confidence: 87%
“…However, for perceived competence, students also feel that virtual reality could improve the knowledge and skill as well as the effort more than traditional text-based materials. The result is aligned with [36] in the context of librarian in public library and also consistent with the research findings of [34], [35] to improve intrinsic motivation for training nurse and medical students.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, Lund and Wang (2019) have shown that librarians can use these technologies to enhance provision of library instruction to their users. Lee et al (2020) concluded in their study that the success or failure of a reality programme in the library does not solely rest on the technology itself but the effort of each librarian in creating social and educational experiences. This might be difficult to achieve as it was found in the current study that funding can influence the adoption of VR and AR in the public libraries.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed the impact AR can have as a driving force to encourage reluctant readers in school libraries. Lee et al (2020) investigated librarians' perspectives on the role of VR in public schools. The research study was carried out in public libraries in the state of Washington using Oculus.…”
Section: Virtual Reality and Augmented Reality In Librariesmentioning
confidence: 99%
“…Findings from this research that are focused exclusively on the librarians views about VR, lessons learned in programming, and challenges faced by librarians can be found in Lee et al (2020) and the practitioner report written by Dahya et al (2019). This paper provides additional information about both patron and librarian perceptions about VR and their experiences with the VR programs.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…The structure of using technology in the library was itself a limitation, given that librarians have a range of responsibilities and this pilot VR program did not include significant prep and technology learning time for the librarians. They were sometimes faced with technical difficulties from computer updates to controllers losing their wireless configuration to the VR system, and having to troubleshoot that on the fly with patrons in front of them (Dahya et al , 2019; Lee et al , 2020). This certainly impacted user experiences and possibly when and which users decided to complete the user experience survey, which we were not always on site to facilitate.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%